Assessment of the Integrity of Reinforced Concrete Beams Strengthened With Carbon Fibre Reinforced Polymer Using the Acoustic Emission Technique - Mat Saliah, S. N.; Md Nor, N. (Frontiers in Mechanical Engineering, 2022)
Today, the use of a non-destructive technique to assess the integrity of reinforced concrete structures strengthened with carbon fibre-reinforced polymer (CFRP) is becoming increasingly important. It is highly important to assess the behaviour of the structure under load. This paper presents the evaluation of a reinforced concrete beam laminated with CFRP at the soffit using the acoustic emission technique. Two types of beams were made, a normal reinforced concrete beam and a reinforced concrete beam laminated with CFRP. CFRP was used to reinforce the bottom part of the beam. The beams were subjected to three-point loading and loaded to failure. During the loading tests, the integrity of the beams was monitored using the acoustic emission technique, and the crack patterns were observed visually. The intensity analysis was carried out on two sensors, designated as CH6 and CH7. CH6 and CH7 were located on top of the beam. Based on the intensity analysis of the acoustic emissions, five intensity crack zones were identified, namely zone A-no crack, zone B-minor, zone C-intermediate, zone D-follow up and zone E-major. With increasing load, which tended to progress the crack modes in the beam, the plots in the intensity zones developed for each crack mode from zone A to zone E. The crack progression matched well with the plots in the intensity zones. Using the intensity zones enables the early detection and prediction of damage.